2018
DOI: 10.1080/15374416.2018.1466307
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Base on Outpatient Behavioral Treatments for Adolescent Substance Use, 2014–2017: Outcomes, Treatment Delivery, and Promising Horizons

Abstract: This article updates the evidence base on outpatient behavioral treatments for adolescent substance use (ASU) since publication of the previous review completed for this journal by Hogue, Henderson, Ozechowski, and Robbins (2014). It first summarizes the Hogue et al. findings along with those from recent literature reviews and meta-analytic studies of ASU treatments. It then presents study design and methods criteria used to select 11 comparative studies subjected to Journal of Clinical Child and Adolescent Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 172 publications
(183 reference statements)
2
97
0
Order By: Relevance
“…Family-based therapies engage parents, caregivers, and siblings in the treatment of adolescent SUDs. Family-based therapies are well-established interventions for treating adolescent SUDs, and are particularly effective at promoting treatment attendance and therapeutic alliance, whereas other treatment modalities have shown only mixed success in these areas [9]. Recent evidence has confirmed that utilizing strategies such as parental monitoring and behavioral management, promoting positive relationships, and encouraging self-regulation and stress management are effective in treating adolescent substance use through family-based approaches [12].…”
Section: A Family-based Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Family-based therapies engage parents, caregivers, and siblings in the treatment of adolescent SUDs. Family-based therapies are well-established interventions for treating adolescent SUDs, and are particularly effective at promoting treatment attendance and therapeutic alliance, whereas other treatment modalities have shown only mixed success in these areas [9]. Recent evidence has confirmed that utilizing strategies such as parental monitoring and behavioral management, promoting positive relationships, and encouraging self-regulation and stress management are effective in treating adolescent substance use through family-based approaches [12].…”
Section: A Family-based Therapymentioning
confidence: 99%
“…CBT is effective in that thoughts, behaviors, and moods are all interconnected, and by providing an adolescent tools to improve problematic thought processes or behaviors, improvements in mood and desirable substance use outcomes often follow. It is well-established as a treatment for adolescent substance use in both individual and group formats [9]. Recent work has focused on third-wave cognitive-behavioral therapies or personalized-delivery of CBT, discussed below in probably efficacious standalone treatments.…”
Section: B Cognitive Behavioral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of MI could be even better in combination with other treatment approaches (Hettema, Steele, and Miller, 2005; Spoelstra, Schueller, Hilton, and Ridenour, 2015; Westra, Aviram, and Doell, 2011; Westra, Constantino, and Antony, 2016), than as a standalone treatment, and combined treatment approaches which MI are advancing (Gates, Sabioni, Copeland, Le Foll, and Gowing, 2016;Hogue, Henderson, Becker, and Knight, 2018;Marker and Norton, 2018;Riper et al, 2014). Motivational Interviewing is often applied at the beginning of treatment and later combined with Cognitive Behavioral Therapies (CBT) as in the project COMBINE (Anton et al, 2006) and in the study reported on in this article: the Elderly study (Andersen et al, 2015).…”
Section: Combined With Other Therapiesmentioning
confidence: 99%
“…Specifically, this model focuses on increasing prorecovery peers and activities in the community to compete with, reduce, and eventually replace substance use with constructive prosocial activities that support the development of recovery capital (Best et al, 2012;Cloud & Granfield, 2008;McKay, 2017). Research on A-CRA has demonstrated that it is effective as primary treatment for youth with substance use problems (Henderson et al, 2016;Hogue, Henderson, Becker, & Knight, 2018) and as continuing care recovery support following residential services (Garner, Godley, Funk, Lee, & Garnick, 2010;Godley et al, 2007Godley et al, , 2014.…”
Section: The Vrsa Modelmentioning
confidence: 99%